THE URGENCY OF MAQASHID SHARIA IN THE DEVELOPMENT OF SHARIA BANKING PRODUCTS - Hendra Hadi; Muhammad Sodiki; Imro Atut Toyyibah; Parman Komarudin (Institut Agama Islam Darussalam Martapura, 2023)
AbstractThe movement and growth of Islamic banking in Indonesia is increasing every year and is in demand by Muslim and non-Muslim customers. This has encouraged Islamic banking to develop its products so that they can compete with conventional banks. However, of course, this must be balanced with knowledge of Islamic maqashid and ushul fiqh in the development of banking products which are sometimes ignored by Islamic financial institutions. As a result, there is rigidity, narrow space for movement and even negligence and errors in inspection and auditing. In this paper using library research methods (library research) with a qualitative approach. The urgency of maqashid in Islamic banking products regulates all fatwas, regulations, financial and banking products as well as fiscal and monetary policies so as not to lose their shari'ah substance. Maqashid syari'ah is a determining factor in creating sharia economic products that can play a dual role (social control tools and socio-economic engineering) to realize the benefit of Muslims. Keywords: Sharia Banking; Maqashid Syariah; Banking Products.